Does Duration of Wearing Face Masks Cause Dry Eye Disease Among Medical Students in Indonesia: A Cross Sectional Study - Angelius, Chelsie; Irma, Josiah; Onasis, Serena; Rizki, Saraswati Anindita; Budimulia, Patricia; Salim, Jonathan; Lesmana, Maria Vashti Zerlinda (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2025)
Introduction: During the COVID-19 pandemic, infection control protocols required universal mask use. At the same time, increased reports of dry eye symptoms emerged. Prior studies showed inconsistent results. This study aims to clarify the association, hypothesizing that prolonged mask wearing is linked to a higher risk of dry eye disease. Methods: This study is an analytical comparative cross-sectional study. The purposive sampling technique was used to collect samples. To diagnose dry eye disease, the Ocular Surface Disease Index (OSDI) questionnaire was used. The cut off score we used is >12 points in OSDI. Two categories were established to assess mask usage duration: <6 hours or ≥ 6 hours per day. Data were collected in January 2023 from 278 respondent medical students in Tangerang, Indonesia. Bivariate chi-square data analysis was performed using SPSS 25.0 software. Discussion: 82 respondents (29.5%) experienced dry eye disease, and 221 respondents (79.5%) used masks for ≥ 6 hours during effective working days along the week. No significant relationship was found between both variables. (OR = 0,883; 95% CI: 0.471-1.658; p = 0.669). Results: There was no association between using masks for a longer period of time to dry eye disease.